Bahasa Melayu lisan dari perspektif jantina dan identitas - Abd Mutalib, Mashetoh (Program Studi Linguistik FIB USU, 2014)
The linguistic situation of the Malay language is characterized by the diversity of the Malay language itself namely the Malay language formal and informal Malay language (dialect, the language of the market, colloquial language, etc.).This linguistic diversity was selected, customized and used in accordance with the needs and circumstances of the community as the communication patterns while the language was being used, particularly in the oral Malay.The situation indirectly showed that the language was closely rebated to the social phenomena surrounding it.Thus, this study identified and explained the diversity of oral Malay language which was determined by the gender aspect in constructing the identity of the language users. The study, which applied the sociological urban dialegtology approach (Labov, 1972; Trudgill, 1974; Milroy, 1987, and Idris, 1995 and 2011), was conducted qualitatively by using the interview analysis.The data were gathered from 34 Malay speakers in the city of Shah Alam.The study found that female gender tended to be more various in the use of lexical aspects.